(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2022)
An extremely important element in the functioning of the enterprise is the competent management of human capital, especially in the tourism economy, where consumers of tourist services deal with an intangible product. The aim of this study is to present the characteristics of the tourism market and the related goals and strategies for human resource management. It describes what human capital is and how it influences the company. The issue of human resource management in tourism is caused by one of the characteristics of the tourism market, which is seasonality, which can be treated as a threat or opportunity for enterprises operating in tourist destinations. The paper describes research on the impact of seasonality on employment in Poland. The ways of using human resources in tourism companies were discussed.